Group Occupational Health Service in a Developing Country - Glanville, H. de (British Medical Journal, 1970)
Summary: In 1967 an experimen:.11 group occupational health service was set up in Dar t!S Salaam to provide direct service to industrial firms. T 3rget companies were visited by a doctor, smaller firn . in rotation by auxiliaries. After three years 65 cornn 1nies had joined with over 15,000 employees, and workers we'e attending the group dispensaries at a rate of over 250,000 visits a year. Such an approach through direct service to the working community appears to be more appropriate to a developing country than a purely advisory central "'lccupariooal health unit.
Keywords: Occupational health service; Dar es Salaam; Tanzania; Dispensaries; Staff clinic